First Aid in Case of Accidents and Emergency Situations: course book - Levchuk, L. P. (GEOTAR-Media, 2017)
Course book highlights nine principle topics of the module "First Aid" as a part of the subject "Health and Safety, Disaster Medicine" and contains key questions for each part as well as provisional tests for the students' self-check. This course book can be helpful for the students taught by means of e-educational systems (including distant learning). The course book is designed for the tertiary medical students taught in English as well as for the foreign students attending classes as a part of the Russian-speaking groups. Besides it can be used as complementary reading by the University students, secondary medical schools students and medical-college students learning English.